1982
DOI: 10.1007/bf02005337
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial energy metabolism in the hypertrophied hearts of spontaneously hypertensive rats

Abstract: Age-related changes in the myocardial energy metabolism were studied in spontaneously hypertensive (SHR) rats of 5-15 weeks of age. Systolic blood pressure increased rapidly during 5 to 10 weeks of age (developing phase) and attained a plateau level at 10 to 15 weeks (sustained phase). Even during the developing phase, the heart was hypertrophic, as assessed by an increase in the ratio of the ventricular weight to body weight. However, myocardial contents of glycolytic intermediates and high energy phosphate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
2

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 20 publications
2
25
2
Order By: Relevance
“…25 Indeed, one study in 25-week-old SHR reported a decrease in Per and an increase in myocardial lactate concentration based on findings in heart biopsy of anesthetized animals. 20 We, however, did not find any difference in the myocardial concentration of high energy metabolite or in myocardial lactate concentration even under isoproterenol stimulation. The differences between the two studies might be due to the experimental conditions.…”
Section: Discussioncontrasting
confidence: 58%
“…25 Indeed, one study in 25-week-old SHR reported a decrease in Per and an increase in myocardial lactate concentration based on findings in heart biopsy of anesthetized animals. 20 We, however, did not find any difference in the myocardial concentration of high energy metabolite or in myocardial lactate concentration even under isoproterenol stimulation. The differences between the two studies might be due to the experimental conditions.…”
Section: Discussioncontrasting
confidence: 58%
“…33 Like diabd tes, LVH is associated with alterations in lipid metabolism 34 - 35 and restricted fuel source availability. 36 - 37 Elevated workloads, reduced coronary reserve, 38 and possibly increased metabolic demand for carnitine 34 (see below) may combine to predispose the hypertrophic ventricle to membranedisrupting effects of diabetes that might otherwise be less apparent in the absence of preexisting LVH.…”
Section: -13mentioning
confidence: 99%
“…Systolic blood pressure (SBP) in SHR rapidly increases between 5 and 10 weeks of age and cardiac hypertrophy develops between 9 and 12 weeks of age (2). Increasing evidence from different experimental models supports the concept that oxidative stress contributes to the pathogenesis of myocardial hypertrophy and the process of myocardial remodeling leading to heart failure (3,4).…”
Section: Introductionmentioning
confidence: 99%